Investigating the Potential of Gamification to Improve Seniors’ Experience and Use of Technology - Minge, Michael; Cymek, Dietlind Helene (Information)
A non-negligible proportion of seniors rarely uses new technology. Far too often, these rather tech unexperienced seniors struggle with new soft- or hard-ware, that do not provide easy access. As a result, some seniors avoid or completely desist to further use “these modern technologies” and consequently miss out on the benefits of digital age. Game-inspired design is supposed to be a promising way to overcome some perceived barriers of seniors by providing hedonic value during early interaction. Previous research has shown that game-inspired design is suitable to motivate seniors’ use of Health-IT. To investigate its potential to facilitate the use of information and communication technology (ICT), an experimental study was conducted. The study investigated the appeal of various gamification features, which were embedded in a prototype of an ICT learning software and compared it to a non-gamified version of the software. Results indicate that the concept of gamified ICT learning software appeals to seniors in general, but that the acceptance of different gamification features is quite diverse. A clear-cut superiority of adding gamification to the software was not found. After interacting with both software versions, seniors in around equal parts preferred either the non-gamified version, the gamified version, or could not decide. Those seniors that clearly favored the gamified version were particularly fond of continuous positive feedback and receiving rewards for each task they have accomplished. Whereas the remaining seniors rather disliked the intensive endorsement through these two features and decided against the gamified version, albeit they liked many of the other game features. Our results underline the necessity of following a user-centered design approach when developing game-inspired applications, and the need for an individualized use of gamification elements to meet the needs of the heterogeneous group of senior users.